Why read Hannah Arendt now - Bernstein, Richard J. 1932-2022 (Polity, 2018)
Inhaltsverzeichnis: Statelessness and refugees -- The right to have rights -- Loyal opposition : Arendt's critique of Zionism -- Racism and segregation -- The banality of evil -- Truth, politics and lying -- Plurality, politics, and public freedom -- The American Revolution and the revolutionary spirit -- Personal and political responsibility.